2016
DOI: 10.3109/21678421.2016.1170149
|View full text |Cite
|
Sign up to set email alerts
|

Patient-ventilator asynchrony, leaks and sleep in patients with amyotrophic lateral sclerosis

Abstract: Sleeping with non-invasive ventilation (NIV) in amyotrophic lateral sclerosis appears to be accompanied by a high patient-ventilator asynchrony (PVA) index. This prospective observational cohort study quantifies PVA and leaks, and searches for effects of these events on sleep after polysomnographic NIV titration. Full-video polysomnography, with incorporation of transcutaneous carbon dioxide and ventilator software, was used to analyse sleep epoch-by-epoch and respiratory events and PVA breath-by-breath in 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 30 publications
0
20
0
11
Order By: Relevance
“…7 Furthermore, Atkeson et al found a high number of episodes of patient-ventilator asynchrony (PVA) (mean ± SD, 69 ± 46 events/h) when NIV was applied in patients with ALS, 9 theoretically harming sleep architecture and sleep quality. In our study, by using in-hospital full-video polysomnography with incorporation of ventilator software during NIV titration, non-bulbar and bulbar patients showed a lower PVA-index of 31 (IQR 15-49) events/h sleep and 32 (IQR 17-55) events/h sleep, respectively, after one month of NIV, 10 and these remaining asynchronies had none to minor impact on sleep architecture. Ensuring good sleep architecture could enhance therapeutic compliance and thereby produce better improvements in quality of life.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…7 Furthermore, Atkeson et al found a high number of episodes of patient-ventilator asynchrony (PVA) (mean ± SD, 69 ± 46 events/h) when NIV was applied in patients with ALS, 9 theoretically harming sleep architecture and sleep quality. In our study, by using in-hospital full-video polysomnography with incorporation of ventilator software during NIV titration, non-bulbar and bulbar patients showed a lower PVA-index of 31 (IQR 15-49) events/h sleep and 32 (IQR 17-55) events/h sleep, respectively, after one month of NIV, 10 and these remaining asynchronies had none to minor impact on sleep architecture. Ensuring good sleep architecture could enhance therapeutic compliance and thereby produce better improvements in quality of life.…”
mentioning
confidence: 61%
“…Our most recent study, using the same titration procedure, showed that only 14% of the patients were positive on this cutoff value for airway obstruction. 10 These data suggest that polysomnographic titration facilitates the adjustment of NIV …”
mentioning
confidence: 89%
“…29 Our current and previous research show, respectively, 23% and 14% of the patients with >5 obstructive events per hour on ST mode. 19 These data suggest that polysomnographic titration probably facilitates the adjustments of NIV settings which could be of major importance on a rapid progressive disease as ALS.…”
Section: Discussionmentioning
confidence: 87%
“…18 Furthermore, it has been shown that PVA remained present even after meticulous polysomnographic NIV titration, nevertheless, without sleep interference. 19 The aim of this randomized cross-over trial was to provide more insight into the NIV titration procedure in patients with ALS. Comparisons in gas exchange, sleep architecture and PVA were made between two different NIV modes: the S mode and ST mode.…”
Section: Summary At a Glancementioning
confidence: 99%
See 1 more Smart Citation